Tachlīlu Mushthalachāt al-Ashami fi al-Mawāqi’ al-Iliktarunī as-Sahmī al-‘Arabiyyati ‘ala Asāsi Murfusimantīk - Badi', Nadal; Kholisin, Kholisin; Mohammad, Ahsanuddin (Universitas Negeri Malang, 2024)
This research aims to describe the stock terms in the Arabic stock websites based on Morphosemantic. Morphosmantic here is a theory of semantics that consists of analyzing morphology and semantics. The researcher used a qualitative descriptive research method. Perform this research using a content analysis form. This research tool is the researcher himself. The data in this search are all sagittal terms (of a word or words) related to morphos mantic in sagittal sites from Saudi Arabia (Saudi Tadawul), Qatar (Qatar Stock Exchange), and UAE (Dubai Financial Market). The results of the research show that the sagittal terms in the Arabic language in morphology have a modification in Arabization, (2) derivatives, (3) types of pluralization, and (4) preference between Arabization and derivatives. And (5) Word Combination, (6) Hybrid, (7) Acronyms and Abbreviations, and in connotation, a modification in (1) the role of connotation in the formation of the meaning of stock terms, and (2) translation (3) change of meaning, (4) relation of meaning, and (5) terminology. يهدف هذا البحث إلى وصف مصطلحات السهم في المواقع الإلكترونية السهمية العربية على أساس مورفوسمانتيك (الدلالة الصرفية). مورفوسمانتيك هنا هو نظرية من نظريات علم الدلالة الذي يتكون من تحليل مورفولوجي (الصرف) وسمانتك (الدلالة). استخدم الباحث بحثا نوعيا بطريقة الوصفي. أداء هذا البحث باستخدام نموذج تحليل المحتوى. أداة هذا البحث الباحث نفسه. البيانات في هذا البحث هي كل المصطاحات السهمية (من الكلمة أو الكلمات) المتعلقة بمورفوسمانتيك في المواقع السهمية من السعودية (تداول السعودية) ، قطر (برصة قطر) والإمارات (سوق دوبي المالي). تظهر نتائج البحث أن المصطلحات السهمية في اللغة العربية في الصرف هناك تعديل في التعريب (Arabization) و(2) الاشتقاق (Derivatives) و(3) أنواع الجمع (Pluralization) و(4) التفضيل بين التعريب والاشتقاق(Preference Between Arabization And Derivatives) و(5) جمع الكلمة (Word Combination) و(6) الهجين (Hybrid) و(7) الأوائلية (Acronyms) والنحت (Abreviations) و في الدلالة تعديل في (1) دور الدلالة في تكوين المعني مصطلحات السهم و(2) الترجمة و(3) تغيير المعنى و(4) علاقة المعنى و(5) الإصطلاحية.